1996
DOI: 10.1021/ic960098b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reduction of Hydrazine to Ammonia with MoFe3S4−Polycarboxylate Clusters. Possible Relevance Regarding the Function of the Molybdenum-Coordinated Homocitrate in Nitrogenase

Abstract: The catalytic function of the previously synthesized and characterized [(L)MoFe(3)S(4)Cl(3)](2)(-)(,3)(-) clusters (L = tetrachlorocatecholate, citrate, citramalate, methyliminodiacetate, nitrilotriacetate, thiodiglycolate) and of the [MoFe(3)S(4)Cl(3)(thiolactate)](2)(4)(-) and [(MoFe(3)S(4)Cl(4))(2)(&mgr;-oxalate)](4)(-) clusters in the reduction of N(2)H(4) to NH(3) is reported. In the catalytic reduction, which is carried out at ambient temperature and pressure, cobaltocene and 2,6-lutidinium chloride are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
68
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 132 publications
(95 reference statements)
0
68
0
Order By: Relevance
“…The role of Mo is evident in Schrocks complex and has often been considered essential for dinitrogen binding by various authors (see also the recent work in references [38][39][40][41][42][43][44]). Very recently, studies on molybdenum complexes have been reported, [45,46] which discuss results for intermediate steps of N 2 reduction in the light of Yandulov and Schrocks Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Mo is evident in Schrocks complex and has often been considered essential for dinitrogen binding by various authors (see also the recent work in references [38][39][40][41][42][43][44]). Very recently, studies on molybdenum complexes have been reported, [45,46] which discuss results for intermediate steps of N 2 reduction in the light of Yandulov and Schrocks Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is used as a rocket fuel, as an antioxidant or as an intermediate for the production of explosives and pesticides [1]. Hydrazine is a strong reducing agent, which reacts easily with metal ions [2]. In the presence of catalysts like Cu(II) and phosphate ions hydrazine radicals are formed via a one-electron oxidation, which ultimately are converted into ammonia and dinitrogen gas (2N P H R C2N P H Q CN R H T CN P +2NH Q .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to understand the mode of action of the enzyme, the chemistry of vanadium centre which contains three sulfur (MS 3 sites) donor atoms is of great importance. So far, limited synthetic models are known that catalyze the conversion of N 2 H 4 to NH 3 , the late stage of ammonia synthesis [9][10][11][12][13][14][15]. Davies and coworkers reported vanadium complexes of the NðCH 2 CH 2 SÞ 3À 3 and OðCH 2 CH 2 SÞ 2À 2 ligands [16].…”
Section: Introductionmentioning
confidence: 99%